Modulated nanofiltration process for pesticides treatment. - Ahmad, Abdul Latif; Abd. Shukor, Syamsul Rizal (Universiti Sains Malaysia, 2008)

(untitled)
In Malaysia, little attention has been given to the presence of pesticides in the water source and its adverse effects on human health. These huge amount of pesticides used, especially in agriculture practice, are the emerging contaminants in drinking water supplies.